J21 The Registry Project: A European Huntington's Disease Network (EHDN) Longitudinal Study of Huntington's Disease. (17th September 2014) - Townhill, J; Fullam, R; McLean, T; Come, A; Burgunder, J; Landwehrmeyer, GB
Abstract : Huntington's disease (HD) is a rare genetic brain disorder leading to abnormal movements, cognitive changes and behavioural disturbances. In order to understand the phenotype better, large cohorts of patients with prospective observational data are needed. REGISTRY, launched in 2004 by the European Huntington's disease Network (EHDN), with the main aims to explore the relationship between clinical characteristics and genetic factors, to expedite identification and recruitment of participants for clinical trials and to develop existing and novel assessment tools to track and predict disease onset and progression. Registry has recruited 11566 participants (75% manifest HD, 15% pre-manifest, 4% at-risk and 6% control participants) at 158 study sites across 20 countries, with data collected by local clinical centres and stored via an internet portal. An extensive range of clinical assessments and biological data are gathered on a wide spectrum of people affected by HD, ranging from those with a positive genetic test but no symptoms through to those with advanced disease. Much knowledge has been gained by analysing the data set. A key strength of Registry, a study strongly supported by lay HD organisations, is its collaborative approach, linking clinicians and scientists, and providing an extensive clinical and biological data repository to facilitate international studies that could not otherwise have been possible. The entire Registry database is available for researchers to conduct data mining projects.